The Relationship Between ANC Visits and Early Detection of High Risk in Pregnant Women at The Wori Health Center - Windy Indrawaty Pusung; Rosyidah Alfitri; Nila Widya Keswara (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2025)
Antenatal Care (ANC) visits are one of the important efforts in early detection of high risk in pregnant women. However, there are still many pregnant women who do not routinely make ANC visits, which can be risky for the health of the mother and baby. This study aims to analyze the relationship between ANC visits and early detection of high risk in pregnant women at the Wori Health Center. This study aims to determine whether there is a relationship between the frequency of ANC visits and early detection of high risk in pregnant women. This study used a quantitative research design with a cross-sectional approach. The study sample consisted of 16 pregnant women respondents registered at the Wori Health Center. Data were collected through interviews and medical record examinations to determine the frequency of ANC visits and the status of early detection of high risk. The statistical test used was the chi-square test with a significance level of 0.05. The results of the chi-square analysis showed a p-value of 0.000, which is smaller than 0.05, which means there is a significant relationship between ANC visits and early detection of high risk in pregnant women at the Wori Health Center. Routine ANC visits have a significant influence on early detection of high risk in pregnant women. Pregnant women who routinely make ANC visits tend to be detected as having high risk sooner, so that appropriate preventive and treatment measures can be taken. It is recommended for the Wori Health Center to increase education regarding the importance of ANC visits for pregnant women, as well as provide adequate facilities to facilitate access for pregnant women in making ANC visits.